Construction of an extended environmental and economic social accounting matrix from a practitioner's perspective - Onil Banerjee; Martín Cicowiez; Renato Vargas; Mark Horridge (Universidad Nacional de La Plata, Centro de Estudios Distributivos, Laborales y Sociales (CEDLAS), 2019)
In 2014, the United Nations published the first International Standard for environmental-economic statistics, known as the System of Environmental-Economic Accounting (SEEA).. As more countries adopt and implement the SEEA, the availability of consistent environmental and economic information increases the need for analytical tools that can use this data to respond to policy relevant questions. In this paper, we present a workflow to develop an environmentally-extended social accounting matrix, which can serve as the basic database for the development of environmentally-extended computable general equilibrium models. To illustrate, and given its comprehensive implementation of the SEEA, we apply this workflow to the Guatemalan case and the Integrated Economic-Environmental Modeling (IEEM) Platform.
Keywords: D58; Q56; 330; Environmentally-extended Social Accounting Matrix; System of Environmental-Economic Accounting Central Framework; Guatemala